SILTING OF FOUM EL GHERZA RESERVOIR - Boualem, Remini; Djillali, Bensafia; Mohamed, Missoum (GeoScience Engineering, 2015)
The Foum El Gherza Reservoir fails to satisfy the irrigation of 300,000 palms of Sidi Okba and Seriana due to advanced siltation. Based on data from bathymetric surveys conducted by the National Agency for Dams, the siltation rate was estimated at 0.9 million m3/year. With a total capacity of 47 million of m3, the Foum El Gherza dam is silted up with more than 65 million m3. In this case, the life of the dam will not exceed 11 years of operation. The total silting of the reservoir will occur in 2023. Desilting the dam proves an emergency to save the palms of Seriana and Sidi Okba.